A perfect square : a Shipshewana Amish mystery - Chapman, Vannetta (Chapman, Vannetta. Shipshewana Amish mystery, 2012)
There's more to the quaint northern Indiana town of Shipshewana than handcrafted quilts, Amish-made furniture, immaculate farms and close-knit families. When a dead girl is found floating in a local pond, murder is also afoot.